PERAN KEMAMPUAN KOMUNIKASI INTERPERSONAL PENDIDIK DALAM MENUMBUHKAN SELF-EFFICACY - Melda Rumia Rosmery Simorangkir (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2019)
ABSTRACT This scientific study aims to describe the role of interpersonal communication abilities of an educator in fostering students' self-efficacy. Although basically, loyal humans do have self-efficacy, but over time in class it is not uncommon in the learning process found students experience confusion, loss of motivation or even difficult to socialize with the environment. This will certainly hinder students in achieving their ideals, students' self-efficacy needs to be regenerated so that students are able to motivate themselves again. Whatever the conditions faced by students, they are still able to focus on the achievement goals. Keywords: educators, interpersonal communication, self-efficacy ABSTRAK Kajian ilmiah ini bertujuan untuk mendeskripsikan peranan kemampuan komunikasi interpersonal seorang pendidik dalam menumbuhkan self-efficacy peserta didik. Walau pada dasarnya setiap manusia memang memiliki self-efficacy, namun seiring berjalannya waktu di kelas tidak jarang dalam proses pembelajaran didapati siswa mengalami kebingungan, kehilangan motivasi atau bahkan sulit untuk berosialisasi dengan lingkungan. Hal ini tentu akan menghambat peserta didik dalam mencapai cita-citanya, self-efficacy peserta didik perlu ditumbuhkan kembali agar peserta didik mampu memotivasi kembali diri mereka. Apapun kondisi yang hadapi siswa tetap mampu focus pada tujuan berprrestasi. Kata Kunci: pendidik, komunikasi interpersonal, self-efficacy